Design, Fabrication And Characterization Of Micro Fluidic And Cmos-Based Process Technology Rf Tuneable Inductor - Hoveizavi, Fatemeh Bani Torfian (2016)
There has been a lot of interest in the tuneability of RF inductors to realize the reconfigurable RF systems for a miniaturized on-chip solution. This approach is still a challenge as high inductance tuning range and high quality factor should be obtained simultaneously. Various prior tuning techniques such as switched turns, switched mutual inductance, bimorph-effect-based varied-coupling and switched magnetic field are studied. The tuning range is less than 60% for state-of-art tunable inductors while the obtained quality factor is low. The research goals of this work are to design a novel tunable inductor with high tuning range and high quality factor for radio frequency wireless applications using microfluids as well as to design a CMOS-based tunable inductor with fine tuning range and high quality factor for microwave wireless applications. Equation-based parametric analysis for planar and three-dimensional inductors are investigated. The contributions of physical and electrical parameters, effective in inductance variation, are determined and new tuning techniques are proposed. The permeable liquids specially the ferrofluids are investigated. Three liquid-based variable inductor including tunable planar spiral inductor, tunable wirewound solenoid inductor and tunable wire-bonded solenoid inductor are proposed. The tunable inductors were simulated and measured with injecting ferrofluids into the core. The liquid-based proposed technique to vary the permeability of the solenoid core showed that using liquids with different magnetic particle concentration varies the inductance significantly while the quality factor degradation is less severe than the prior works. Using the ferrofluids with different magnetic Nano-particle concentration injected to PDMS-based channel, different tuning range and self-resonance frequencies were obtained. The measured tuning ratio for the wire-wound inductor was obtained around 90.6% with a maximum Q factor of 129. The tuning ratio for the wirebonded inductor was measured as 81% with a maximum quality factor of 39.8. Besides, the proposed fine-tunable 0.11-μm CMOS structure to control the magnetic flow in the planar inductors was simulated and measured. The inductance can be tuned for 9 different values and a tuning range of 6.5% is obtained at 1.7 GHz. In addition, in order to miniaturize the inductor, the MEMS process to realize 3D solenoid inductor on tiny scales is proposed. The quality factor in all proposed designs are remained in acceptable range for high-frequency wireless applications. Also, the measured results for CMOS-based proposed technique showed the quality factor is intact while fine tuning ratio is achieved.